The multilayered regulation of aromatic amino acid biosynthesis in plants - El-Azaz, Jorge; Maeda, Hiroshi A. (Trends in biochemical sciences (Amsterdam. Regular ed.), 2025)
Plants commit large amounts of carbon and energy to the biosynthesis of aromatic amino acids (AAAs), because these molecules are precursors to a multitude of natural chemicals and polymers that are crucial for plant adaptation to the environment.The biosynthesis of AAAs starts with the shikimate pathway, which produces chorismate from phosphoenolpyruvate and erythrose-4-phosphate. Then, the biosynthesis of tryptophan and of phenylalanine and tyrosine from chorismate proceed via different pathways.Plants have multiple mechanisms to regulate key enzymes in the AAA biosynthetic pathway. These regulatory mechanisms are more complex than in other AAA-producing organisms, such as bacteria and yeast, allowing plants to precisely control AAA biosynthesis depending on the environment, tissue type, and other factors.Understanding the regulation of key AAA biosynthetic enzymes has allowed us to unlock the regulation of this pathway and generate engineered plants that overproduce AAAs. These engineered plants provide a promising chassis to sustainably produce useful AAA-derived chemicals in planta. The shikimate and aromatic amino acid (AAA) biosynthetic pathways are crucial for the production of L-phenylalanine (Phe), L-tyrosine (Tyr), and L-tryptophan (Trp), as well as vitamins, hormones, and an array of plant natural products, including lignin, a major reservoir of organic carbon on Earth. In this review, we summarize recent advances in the mechanisms that dynamically regulate multiple enzymatic isoforms in plant AAA biosynthetic pathways, with a particular focus on Phe biosynthesis due to its central role as a precursor to phenylpropanoids. The integration of AAA biosynthesis with upstream and downstream plant metabolism is also discussed, as well as how this fundamental knowledge can inform the bioengineering of plant-based platforms for sustainable production of AAA-derived natural products. The shikimate and aromatic amino acid (AAA) biosynthetic pathways are crucial for the production of L-phenylalanine (Phe), L-tyrosine (Tyr), and L-tryptophan (Trp), as well as vitamins, hormones, and an array of plant natural products, including lignin, a major reservoir of organic carbon on Earth. In this review, we summarize recent advances in the mechanisms that dynamically regulate multiple enzymatic isoforms in plant AAA biosynthetic pathways, with a particular focus on Phe biosynthesis due to its central role as a precursor to phenylpropanoids. The integration of AAA biosynthesis with upstream and downstream plant metabolism is also discussed, as well as how this fundamental knowledge can inform the bioengineering of plant-based platforms for sustainable production of AAA-derived natural products.